ANALISIS STRATEGI SISTEM PEMUNGUTAN PAJAK REKLAME DALAM UPAYA MENINGKATKAN PENERIMAAN PAJAK DAERAH KOTA DEPOK - Wicaksono, Reza Aulia; Andrayanti, IIn (Jurnal Ilmu Administrasi Publik, 2025)
Local taxes and levies are the important sources of revenue for the regional government in organizing governance and community services. High local revenue reflects good resources management and can be used to develop public facilities and social activities. According to Koteen (in Salusu, 1996), there are several strategies such as organizational strategy, program strategy, supporting resources strategy, and institutional strategy. SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis was used to evaluate the institution condition. The aim of this research is to find out which strategies used by the regional financial agency (Badan Keuangan Daerah—BKD) of Depok to deal with obstacles and efforts that can be made related to the billboard tax billing system in the city of Depok. Based on the analysis, organizational and institutional strategies had been run well, but the program strategy needed to improve its billboard tax socialization. Supporting resources strategy needed additional training for the employees, and the monitoring and administration in internal and external factors had to be tightened to improve the legal compliance and effectiveness, the realization of billboard tax in the last 4 years, namely from 2019 to 2022, had continued to increase, and the most significant is the revenue in 2022 which was Rp 36,909,071,794 however the realization of bilboard tax revenue had decreased, so that there needed several special strategies to escalate the realization of revenue in the regional financial agency (Badan Keuangan Daerah—BKD) of Depok. Obstacles dealt with included billboard tax objects installed without permission, lack of bilboard taxpayers in fullfillingthe billboard tax obligations, public non- compliance in paying billboard taxes. Efforts made were to continue conducting socialization and education on billboard tax billing to increase taxpayers’ awareness, to improve resources by conducting training and optimizing the owned technology and to carry out regular  evaluation to amend errors occured.